Main principles of surgical treatment in malignant spinal tumors - Vyrva, Oleg (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
The author highlights the modern vision of the basic principles of replacing bone and joint defects during surgical treatment of patients with malignant tumors of bones. He emphasizes the need and effectiveness of an interdisciplinary approach to the definition of a tumor process and the use of a full-scale preoperative examination and all treatment methods in accordance with approved international protocols. One of the main methods of treatment of malignant bone tumors is considered organ salvage surgery, and only in the presence of contraindications - amputation. The classification of surgical interventions, their characteristics, difficulties during execution, application for replacement of postreaction defects of bones and joints of allografts or modular tumor endoprostheses is given. The necessity to adhere to the basic principles of bone oncosurgery and protocols of specific therapy for successful treatment is emphasized.